(untitled) (Avocetta, 2025)
This study examines the population dynamics and spatial distribution of Arctic Terns in two tourist sites in Iceland’s Westfjords: Vigur Island and Súðavík. In 2023, counts revealed 458 terns in Súðavík and 991 in Vigur. We propose a monitoring approach using photography to estimate the population, including non-breeders. Additionally, an interspecies interaction was observed in Vigur, where terns appear to be relocating towards the puffin colony. This behaviour is hypothesised to serve as a defence mechanism against predators, utilising the puffins’ frequent, low-altitude flights, as a protective ceiling.